ANALISIS KELAYAKAN PENAMBAHAN MESIN CETAK DI PERCETAKAN GRAND DEPOK PRINTING - Sumardi; Septiana Hadiamin (Pusat Riset dan Inovasi Nasional, 2022)
This research is done to find out whether it is feasible or not if this research is done to find out whether it is feasible or not if the Grand Depok Printing printing business adds investment in the procurement of new printing presses. The data used is to use an estimate of initial capital investment analysis. The analysis tool used is the Payback period (PP) method. Net Present Value (NPV), Internal Rate Of Return (IRR), and Profitability Index (PI) and investigate aspects in business feasibility studies namely Legal Aspects, Market and Marketing Aspects, Technical / Operations Aspects, Financial Aspects, Management / Organization Aspects, Social Economic Aspects, Environmental Dumpak Aspects. The results of calculations obtained are Payback period for 7 Months and 20 days, Net present value of RP. 8,545,174,145, Internal Rate Of Return of 22.15%, and Prifitability Index of 1,541. Therefore, it can be decided that the procurement of new printing presses at The Grand Depok Printing business in Verbena Shophouse, Grand Depok City, Jl. Boulevard Grand Depok City, Tirtajaya, Kec. Sukmajaya, Depok City, West Java 16412 is worth running..